2014
DOI: 10.4149/endo_2014_01_25
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio may be superior to C-reactive protein for predicting the occurrence of postmenopausal osteoporosis

Abstract: Our data indicate that NLR may be a better predictor than CRP for occurrence of osteoporosis in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 0 publications
3
42
1
5
Order By: Relevance
“…In this context, it has been suggested a synergistic effect of hyperglycemia and coeliac autoimmunity on low BMD [58]. Although Post-M presented more comorbidities (Table 2) and osteoporosis (Table 3) and, overall, subjects with osteoporosis had higher recent NLR compared to patients with osteopenia or normal BMD (Table 4), as previously reported [54], Pre-MPP had higher recent NLR (Table 5).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this context, it has been suggested a synergistic effect of hyperglycemia and coeliac autoimmunity on low BMD [58]. Although Post-M presented more comorbidities (Table 2) and osteoporosis (Table 3) and, overall, subjects with osteoporosis had higher recent NLR compared to patients with osteopenia or normal BMD (Table 4), as previously reported [54], Pre-MPP had higher recent NLR (Table 5).…”
Section: Discussionsupporting
confidence: 77%
“…From 50 subjects, after the selection for anti-Tg at diagnosis, we retrospectively evaluated 46 adult-diagnosed (Table 2) coeliac disease patients at GFD. In this study, we evaluated NLR, being a marker of inflammation in coeliac disease [8, 9] related to postmenopausal osteoporosis [8, 54].…”
Section: Discussionmentioning
confidence: 99%
“…Fisher et al,21 stated that high N/L displayed as a potential indicator of bone fracture. Although Yılmaz et al,22 showed that N/L and CRP were significantly higher in the osteoporotic group than in the control group, N/L was found to be more effective for predicting PMO than CRP. There is only one study exploring the association of P/L and PMO along with N/L 23.…”
Section: Discussionmentioning
confidence: 86%
“…A recent study conducted by Yilmaz et al indicated that NLR was better than CRP for predicting the occurrence of osteoporosis [35]. Several potential mechanisms may explain the association between NLR and cardiovascular disease: neutrophils are proinflammatory cells, which could aggravate endothelial dysfunction, activate macrophages, and promote foam cell formation [36]; meanwhile, lymphopenia is associated with the progression of atherosclerosis and adverse cardiovascular outcomes, which may be due to the apoptosis of lymphocytes [37].…”
Section: Discussionmentioning
confidence: 99%